A comparison of valuation methods for cultural ecosystem services in support of ecosystem accounting - Anna Bronzes; Lars Hein; Rolf Groeneveld; Alim Pulatov (One Ecosystem)
Assigning an economic value to cultural ecosystem services is important to promote their sustainable and rational use. Valuation of such services requires a non-market approach as they are not traded on markets and, thus, have no directly observable market price. The System of Environmental-Economic Accounting – Ecosystem Accounting (SEEA-EA) aims to develop a systematic approach to value ecosystem services aligned with the valuation approach of the national accounts. However, valuing cultural services in SEEA-EA is challenging and different approaches have been developed. In this study, we compare four prominent approaches for valuing cultural ecosystem services: resource rent, travel cost method, simulated exchange value and consumer expenditure. We test and compare these methods in a case study of Ugam Chatkal State Nature National Park in Uzbekistan and examine to what degree the methods are aligned with accounting valuation principles. We note that the methods assess value in a different way and, accordingly, we find considerable differences amongst approaches in recreational value: values ranged between US$1.62M and US$65.19M annually. The lowest value was provided by the resource rent approach and the highest value by the travel cost method including consumer surplus. This latter method is not aligned with SEEA-EA accounting; however, even the three methods that are aligned with accounting principles provide quite different value estimates. The two other approaches, simulated exchange value and consumer expenditure, provided an annual value of US$24.46M and US$13.5M, respectively. We find that a resource rent method is likely to underestimate the 'true' value of the service when used for accounting and that the simulated exchange value method seems to be best aligned with the valuation needs for cultural services for SEEA-EA.